2020
DOI: 10.1101/2020.08.02.233254
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NPC1-mTORC1 signaling Couples Cholesterol Sensing to Organelle Homeostasis and is a Targetable Pathway in Niemann-Pick type C

Abstract: Lysosomes promote cellular homeostasis through macromolecular hydrolysis within their lumen and metabolic signaling by the mTORC1 kinase on their limiting membranes. Both hydrolytic and signaling functions require precise regulation of lysosomal cholesterol content. In Niemann-Pick type C (NPC), loss of the cholesterol exporter, NPC1, causes cholesterol accumulation within lysosomes, leading to mTORC1 hyperactivation, disrupted mitochondrial function and neurodegeneration. The compositional and functional alte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 91 publications
(140 reference statements)
3
32
0
Order By: Relevance
“…While multiple cargo receptors are recruited to damaged lysosomes (Figure 4C-E) (Davis et al, 2021;Koerver et al, 2019;Papadopoulos et al, 2017), to date, the cargo receptors critical for linking damaged lysosomes to the core autophagy machinery have not been clearly delineated, although knockdown of SQSTM1 has been reported to result in reduced lysophagic flux (Papadopoulos et al, 2017). We therefore systematically probe cargo receptor involvement in lysophagy.…”
Section: Measurement Of Lysophagic Flux With Lyso-keimamentioning
confidence: 99%
See 1 more Smart Citation
“…While multiple cargo receptors are recruited to damaged lysosomes (Figure 4C-E) (Davis et al, 2021;Koerver et al, 2019;Papadopoulos et al, 2017), to date, the cargo receptors critical for linking damaged lysosomes to the core autophagy machinery have not been clearly delineated, although knockdown of SQSTM1 has been reported to result in reduced lysophagic flux (Papadopoulos et al, 2017). We therefore systematically probe cargo receptor involvement in lysophagy.…”
Section: Measurement Of Lysophagic Flux With Lyso-keimamentioning
confidence: 99%
“…In addition, multiple Ub-binding cargo receptors including OPTN, CALCOCO2 and TAX1BP1 are recruited to ubiquitylated bacteria and are required for efficient xenophagy in various contexts (Thurston, 2009a;Thurston et al, 2012;Tumbarello et al, 2015;Wild et al, 2011). While multiple cargo receptors including have been reported to be recruited to damaged lysosomes (Bussi et al, 2018;Davis et al, 2021;Koerver et al, 2019), the underlying mechanisms for recruitment, the identity of the receptors critical for lysophagic flux, and the reasons for the diversity of receptors that are recruited remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…3A). Zoncu and colleagues (Davis et al, 2021) have shown that NPC1 loss elevates mTORC1 signaling, and inhibition of mTORC1 can improve lysosome proteolytic capacity without correcting cholesterol accumulation. Here, loss of the negative regulatory activity of the GATOR1 complex may show a worse phenotype because of dysregulation of hyperactive mTORC1.…”
Section: Resultsmentioning
confidence: 99%
“…Zoncu and colleagues have shown that blocking NPC1 function hyperactivates mTORC1 and leads to accumulation of accessible cholesterol on the outer leaflet of lysosomes, highlighting a cholesterol transfer pathway from the ER to the lysosome outer leaflet (Lim et al, 2019; Davis et al, 2021). Somehow, loss of SNX13 enables cholesterol transfer to the plasma membrane despite the absence of NPC1 function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation